Pengaruh Transaksi Jual-Beli Emas Non-Fisik (Online) Melalui Trading - Nasrawati; Rayyani Waode (CV. ITTC INDONESIA, 2025)
Online gold trading is a rapidly growing phenomenon along with technological advances and increasing public interest in gold investment. This development offers unprecedented convenience and efficiency, but also presents new challenges and risks that need to be understood. This mini-research will discuss the background to the emergence of online gold trading, its advantages and disadvantages, and its implications for the gold market as a whole. Development of Traditional Gold Investment Before the digital era, gold trading was carried out conventionally through physical gold shops. Transactions were carried out face-to-face, with a relatively time-consuming process and sometimes less transparent in terms of pricing. Nevertheless, gold remains a popular investment choice because of its relatively stable and liquid nature. Public trust in gold as a safe haven asset is also a driving factor. The Emergence of Online Gold Trading. The development of internet technology and e-commerce has revolutionized the way people transact, including in gold trading. Online platforms offer easy access, higher price transparency because they are directly connected to the global market, and time and cost efficiency. Various platforms, both those that specifically sell gold and general marketplaces, offer a variety of gold product choices, from gold bars to jewelry. This expands access to gold investment for the wider community, without geographical limitations.